Magnetisation reversal in Ca2PrCr2NbO9 and Ca2PrCr2TaO9 - Hunter, E; Mousdale, S; Battle, P; Avdeev, M (Elsevier, 2018)
Polycrystalline samples of the perovskites Ca2PrCr2BO9 (B=Nb, Ta) have been synthesised using the standard ceramic method and characterized by x-ray diffraction, neutron diffraction and magnetometry. Both crystallise in the orthorhombic space group Pnma and exhibit magnetisation reversal when field-cooled in an applied field of 100 Oe. The absolute value of the negative magnetisation at 2 K in an applied field of 100 Oe is an order of magnitude greater in Ca2PrCr2TaO9 than it is for Ca2PrCr2NbO9. Magnetometry and powder neutron diffraction showed that the Cr3+ cations in Ca2PrCr2NbO9 and Ca2PrCr2TaO9 order in a GyFz magnetic structure below 110 and 130 K, respectively. The Pr3+ cations remain paramagnetic down to ~10 K and show no-long range order at 2 K. Both compounds show a large degree of hysteresis in M(H), with coercive fields of 3.79 kOe and 3.03 kOe at 2 K.